Sustainability of Overlapped Emission Trading and Command-And-Control CO2 Regulation for Korean Coal Power Production: A DEA-Based Cost-Benefit Analysis - Yang, Fan; Choi, Yongrok; Lee, Hyoungsuk; Debbarma, Jahira (Frontiers in Environmental Science, 2022)
Regulatory policies are indispensable to efficiently curbing anthropogenic CO2 emissions and sustainably producing emission-intensive goods. Though previous modelling practice has studied the cost and benefit of different regulatory policies, such as command-and-control (CAC) and emission trading scheme (ETS), little is known about that for overlapped emission regulation policies. Here, we built up a Data Envelopment Analysis model to study the losses and gains from the overlapped implementation of CAC and ETS for Korean coal-fired power plants during 2011-2015. We showed that the initial phase of CAC in 2012 caused a sudden loss in power plants’ output, but that the loss was gradually eliminated in 2013 and 2014. Upon promulgation in 2015, ETS is expected to increase only 0.990% of output compared to CAC, yet it largely failed to deliver the potential benefit in its first year. The overlapped implementation of CAC and ETS contributes to a small share (5.567%) of the unrealized benefit. Nonetheless, we showed that implementing CAC and ETS in parallel tends to disproportionately affect less efficient power plants by restricting their strategies to meet regulatory measures. Therefore, we suggest that the integration of CAC and ETS can be a transitory measure as ETS provides only marginal welfare benefits, but ETS must be fully adopted and strengthened in the near future to economically and equitably mitigate CO2 emissions.